Latest advancement of technologies in supply chain management : an overview - Nizaroyani Saibani,; Jaharah A. Ghani,; Muhammad Hassan Shamsul Akmar,; Wa, Kai Boon; Mohan Raj Ravi,; Muhammad Azim Md Nawawi,; Nur Aziatul Izwa Mohd Asri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Supply chain management (SCM) involves an interconnected structure of facilities that produces elements or compounds for transforming into a semifinished compound. After completion, the final compound is delivered to customers via a distribution system. Owing to ever-changing customer demands, increasingly efficient and resilient SCM is necessary, which requires support from the latest technologies. Therefore, this paper presents an overview of the latest technologies in SCM and logistics. The management of a supply chain and role of the different actors involved differ from industry to industry and company to company. Consequently, SCM has become a crucial issue to manufacturers, professionals and researchers. The latest technologies identified in this paper include radio frequency identification, vehicular ad hoc networks, the Internet of things, robotics and artificial intelligence and blockchain. Moreover, the application of the aforementioned technologies in different industries and systems is discussed to understand how the technologies impact practitioners. Although not discussed thoroughly, other recent technology trends in SCM and logistics, such as machine learning, autonomous vehicles/drones, advanced analytics, cloud logistics, supergrid logistics, anticipatory logistics, omnichannel logistics and additive manufacturing (3D printing), are also highlighted in this paper. By understanding the advancements in SCM technology, the possible direction of future innovations can be effectively planned and articulated.